2017
DOI: 10.1021/acs.orglett.7b01701
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Synthesis of 4-Aminoquinolines and [1,3] N-to-C Rearrangement to Quinolin-4-ylmethanesulfonamides

Abstract: A copper-catalyzed regiocontrolled three-component reaction afforded diversified 4-aminoquinolines using nitriles, diaryliodoniums, and ynamides. The C7-substituted regioisomers were formed regioselectively when meta-substituted phenyliodonium salts were used. [1,3] N-to-C rearrangement of the products to quinolin-4-ylmethanesulfonamides and simultaneous deprotection of benzyl and sulfonamide group were newly developed. Finally, antimalarial CK-2-68 was successfully prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“… 21 Finally, we recently showed that palladium-catalyzed oxidative isocyanide insertion of N- aryl imines by double C–H activation also affords 4-AQs. 22 However, these methods rely on rather specialized starting materials 17 20 and/or afford the desired 4-AQs in disappointing yields. 18 , 22 Most diversity-oriented routes toward 4-AQs rely on the amination of 4- haloquinolines, 23 , 24 in turn derived from the corresponding 4-quinolones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Finally, we recently showed that palladium-catalyzed oxidative isocyanide insertion of N- aryl imines by double C–H activation also affords 4-AQs. 22 However, these methods rely on rather specialized starting materials 17 20 and/or afford the desired 4-AQs in disappointing yields. 18 , 22 Most diversity-oriented routes toward 4-AQs rely on the amination of 4- haloquinolines, 23 , 24 in turn derived from the corresponding 4-quinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, there is great interest to efficiently access the 4-AQ core, and over the past decades, several cascade reactions toward these medicinally valuable scaffolds have been developed (Scheme ). For example, 4-AQs can be obtained from the reaction of ynamides and nitrilium species, resulting from either arylation of nitriles or dehydration of anilides . The Cu­(I)-catalyzed cyclization of imidoylacetylenes and sulfonyl azides affords 4-AQs, as well .…”
Section: Introductionmentioning
confidence: 99%
“…[9] Several synthetic approaches have been reported for 4-aminoquinoline, which include the Friedlander reaction, [10] reduction of 4-azidoquinoline, [11] Buchwald-Hartwig amination. [12] Other alternative routes for access of 4-aminoquinolines were multi-component reaction, [13] metal-catalyzed cascade reaction, [14] and cyclization with ynamides. [15] In a similar context, Liu et al, developed Cu(II)-catalyzed desulfitative 6π electro-cyclization reaction for the synthesis of 4aminoquinolines (Scheme 1a).…”
mentioning
confidence: 99%
“…The effect of other bases was also investigated. For example, Inorganic bases such as Li t OBu, Cs 2 CO 3 , KOH, NaOH, K 3 PO 4 make possible the desired product 3 a in relatively lower yields (Table 1, entries [14][15][16][17][18]. Furthermore, when organic base such as DBU and DABCO was employed in the reaction, only DBU was found effective to deliver the desired product in acceptable yield (Table 1 entries [19][20].…”
mentioning
confidence: 99%
“…[1,2] Further activation of ynamides often relies on their reaction with Brønsted [3] or transition metal pacids [4] to form keteniminium ions [1a, 5] providing superb reactivity within addition and/or annulation processes. Such approaches were particularly realized in the emerging gold catalysis of ynamides [6] leading to indoles [7,8] and quinolines [9,10] with different substitution pattern. Protocols aiming at generating reactive neutral ketenimines [11] from ynamides have been less explored.…”
mentioning
confidence: 99%